Recent progress on coatings of biomedical magnesium alloy - Peiduo Tong; Yulong Sheng; Ruiqing Hou; Mujahid Iqbal; Lan Chen; Jingan Li (Smart Materials in Medicine, 2022)
Magnesium (Mg) alloy has received thorough attention in the biomedical field due to its excellent mechanical properties, good biocompatibility, and biodegradability. However, Mg alloy usually shows excessive degradation rate in the physiological environment owning to its active chemical nature. At the same time, the hydrogen generated by the degradation of Mg will increase the pH of local tissues, which will harm the growth of surrounding tissues. Given the above problems, it has become a research hotspot to obtain various properties of Mg alloy for clinical application by surface modification. In this paper, the surface coatings of Mg alloy are reviewed according to different types, including metals (metal oxides, metal hydroxides), inorganic non-metals, polymers (synthetic polymers and natural polymers), and composite coatings. The preparation methods, corrosion resistance, and biocompatibility of different types of coatings are discussed, and the development prospect of biomedical Mg alloy surface coatings is also predicted.